2016
DOI: 10.1126/science.aaf7066
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for membrane anchoring of HIV-1 envelope spike

Abstract: HIV-1 envelope spike (Env) is a type I membrane protein that mediates viral entry. We use NMR to determine an atomic structure of the transmembrane (TM) domain of HIV-1 Env reconstituted in bicelles that mimic a lipid bilayer. The TM forms a well-ordered trimer that protects a conserved membrane-embedded arginine. An N-terminal coiled-coil and a C-terminal hydrophilic core stabilize the trimer. Individual mutations of conserved residues did not disrupt the TM trimer and minimally affected membrane fusion and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
254
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 172 publications
(270 citation statements)
references
References 49 publications
14
254
1
1
Order By: Relevance
“…Both the gp41 membrane-proximal external region and the transmembrane segment are disordered in the PGT151-EnvΔCT complex structure (48). As both of these gp41 regions have been implicated in maintaining the conformation of the native HIV-1 Env in state 1 (35,41,55,(82)(83)(84), the observed disorder makes it unlikely that the state 1 conformation is represented by the EnvΔCT structure (or, on the basis of its close resemblance, by the soluble gp140 SOSIP.664 structure).…”
Section: Discussionmentioning
confidence: 97%
“…Both the gp41 membrane-proximal external region and the transmembrane segment are disordered in the PGT151-EnvΔCT complex structure (48). As both of these gp41 regions have been implicated in maintaining the conformation of the native HIV-1 Env in state 1 (35,41,55,(82)(83)(84), the observed disorder makes it unlikely that the state 1 conformation is represented by the EnvΔCT structure (or, on the basis of its close resemblance, by the soluble gp140 SOSIP.664 structure).…”
Section: Discussionmentioning
confidence: 97%
“…A proposed nuclear magnetic resonance (NMR) structure identified the tyrosine-based YXXL sorting signal as being located within a hydrophilic core of transmembrane domain (TMD) of gp41, contributing to stabilize the trimeric structure TMD. Mutation of this motif is suggested to destabilize the hydrophilic core of TMD trimer, altering the antigenic surfaces of the ectodomain of gp120 (67). Thus, an attractive model to explain the changes in the neutralization sensitivity of the YXXL mutant viruses is that this membrane-proximal internal motif is involved in allosteric modulation of gp120.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, like many other soluble Env preparations (12,29), it does not fully recapitulate the antigenic structure of virion-borne Env. Our recent observation that the TMD of HIV-1 Env is a structural component critical for the stability of the functional Env spike provides a plausible explanation for why the antigenic properties of most recombinant, soluble Env preparations with the TMD deleted deviate from those of the native protein (14,39). We therefore must take the structural constraints imposed by the TMD on the ectodomain into consideration when designing a soluble immunogen, e.g., by mutating surface-exposed, lipid-interacting hydrophobic residues on the TMD while maintaining the trimeric structure seen in the high-resolution structure (14,40).…”
Section: Discussionmentioning
confidence: 99%
“…We found that deletion of the CT has minimal impact on the membrane-fusion function of the Env trimer but has an unexpectedly large influence on the antigenic properties of the ectodomain (10). Moreover, to understand the physical coupling between the CT and the ectodomain, we then determined an atomic structure of the transmembrane domain (TMD) (14). The TMD forms a well-ordered trimer.…”
mentioning
confidence: 99%